Exploring the epistemic and ontic conceptions of Models and Idealizations in Science - Gonzalez Barman, Kristian (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2023)
Book review: Alejandro Cassini & Juan Redmond (eds.), Models and Idealizations in Science: Artifactual and Fictional Approaches, Springer Iternational Publishing, Cham 2021, pp.xv+270.